FAMILY-BASED SCHOOL AS A MODEL FOR PEACE EDUCATION - A.A.Ngr. Eddy Supriyadinata Gorda; Kadek Devi Kalfika Anggria Wardani; Ida Bagus Arya Lawa Manuaba (Journal on Studies in English Language Teaching (JOSELT), 2020)
As a multicultural country with variegated sociso-cultural condition and vast geographical area, it could be stated that Indonesia has high potential to both horizontal and vertical conflicts. Therefore, Indonesia needs a strategy to preserve diversity and to prevent it to turn to conflicts. Peace education program is one kind of intervention which can assist Indonesia to manage its diversity. This article discusses about concept of family-based school as an alternative to peace education model. Data collecting was done by observation and interviews at Junior High SchoolNasional Denpasar which has been applying family-based school to develop peace education. Discussion in this article is divided into two main parts. Firstly, there is a theoretical perspective of how a family-based school should be to internalize peace values to the students. In the second part, kinds of activities directing to associative actions of disseminating peace values are described. By focussing on the two topics, this article is expected to give an alternative model for organizing peace education in Indonesia. Along with the increasing tendency of multicultural conflicts to occur in Indonesia, the urgency of peace education is getting higher.